ASPEK HUKUM ISLAM DALAM PENGELOLAAN MAKAM ULAMA SEBAGAI DESTINASI WISATA RELIGI DI BATU LAYANG PONTIANAK - Marhaban Marhaban; Firdaus Achmad; Abu Bakar (Al-Aqad, 2023)
This research aims to analyze the development of Batu Layang tomb from a pilgrimage center to a religious tourism destination and how the aspects of Islamic law in the management of ulama tombs as religious tourism destinations in Pontianak City. This type of research is field research with qualitative methods and a juridical-empirical approach. The research data source uses primary data in the form of interviews with religious leaders of MUI West Kalimantan while secondary data is in the form of journals, books, theses, and articles related to legal aspects in the management of ulama tombs. The researcher concluded that: 1) The development was also promoted in online media and received many visits in various regions. This was followed by changes in the governance of Batu Layang and the emergence of local businesses. At that limit, Batu Layang opened up jobs and economic activity. This economic development is one of the objectives of RI Law No. 10/2009 and the interests of the Pontianak local government. 2) The aspect of Islamic law in the management of Batu Layang's tomb as a religious tourism destination is considered valid by MUI religious leaders.